2023
DOI: 10.1007/s43630-023-00394-5
|View full text |Cite
|
Sign up to set email alerts
|

Nanosponge-C3N4 composites as photocatalysts for selective partial alcohol oxidation in aqueous suspension

Abstract: A set of four composite materials was prepared, consisting of a nanosponge matrix based on β-cyclodextrin in which carbon nitride was dispersed. The materials were characterized by the presence of diverse cross-linker units joining the cyclodextrin moieties, in order to vary the absorption/release abilities of the matrix. The composites were characterized and used as photocatalysts in aqueous medium under UV, visible and natural solar irradiation for the photodegradation of 4-nitrophenol, and for the selective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…in nanoparticle form [11][12][13][14][15][16][17][18][19][20] is associated with a carbonaceous material such as graphene (G), graphene oxide (GO), or reduced graphene oxide (RGO) [21][22][23][24][25][26]. We have recently shown that significant activity enhancement can be achieved in this context by associating the photoactive species with a functional sorbent material such as a nanosponge (NS) [27,28]. In brief, NSs [29][30][31] are hyper-reticulated polymers constituted by supramolecular host units-cyclodextrins (CDs) in the most common cases, but also calixarenes (CAs) occasionally [32,33]-held together by suitable linker units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…in nanoparticle form [11][12][13][14][15][16][17][18][19][20] is associated with a carbonaceous material such as graphene (G), graphene oxide (GO), or reduced graphene oxide (RGO) [21][22][23][24][25][26]. We have recently shown that significant activity enhancement can be achieved in this context by associating the photoactive species with a functional sorbent material such as a nanosponge (NS) [27,28]. In brief, NSs [29][30][31] are hyper-reticulated polymers constituted by supramolecular host units-cyclodextrins (CDs) in the most common cases, but also calixarenes (CAs) occasionally [32,33]-held together by suitable linker units.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, six different composite photocatalysts were obtained (indicated as Cat1-Cat6), the performances of which were compared to those of plain RGOAg. We have recently shown that significant activity enhancement can be achieved in this context by associating the photoactive species with a functional sorbent material such as a nanosponge (NS) [27,28]. In brief, NSs [29][30][31] are hyper-reticulated polymers constituted by supramolecular host units-cyclodextrins (CDs) in the most common cases, but also calixarenes (CAs) occasionally [32,33]-held together by suitable linker units.…”
Section: Introductionmentioning
confidence: 99%